2023
DOI: 10.3390/ma16144992
|View full text |Cite
|
Sign up to set email alerts
|

Reset-First and Multibit-Level Resistive-Switching Behavior of Lanthanum Nickel Oxide (LaNiO3−x) Thin Films

Abstract: The resistive random-access memory (RRAM) with multi-level storage capability has been considered one of the most promising emerging devices to mimic synaptic behavior and accelerate analog computations. In this study, we investigated the reset-first bipolar resistive switching (RS) and multi-level characteristics of a LaNiO3−x thin film deposited using a reactive magnetron co-sputtering method. Polycrystalline phases of LaNiO3 (LNO), without La2O3 and NiO phases, were observed at similar fractions of Ni and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Moreover, Wan Jing et al [7] investigated the RS behavior of PLD-fabricated LaCrO 3 thin films, revealing unipolar switching behavior with a high resistance ratio and excellent endurance and retention characteristics. Additionally, T Kim et al [20] showed that the fabricated TiN/LaNiO 3−x /Pt RRAM devices exhibited reset-first RS behavior and gradual resistance changes under AC pulse application, making them suitable for low-power synaptic devices in neuromorphic computing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wan Jing et al [7] investigated the RS behavior of PLD-fabricated LaCrO 3 thin films, revealing unipolar switching behavior with a high resistance ratio and excellent endurance and retention characteristics. Additionally, T Kim et al [20] showed that the fabricated TiN/LaNiO 3−x /Pt RRAM devices exhibited reset-first RS behavior and gradual resistance changes under AC pulse application, making them suitable for low-power synaptic devices in neuromorphic computing.…”
Section: Introductionmentioning
confidence: 99%